Tingkat Pengetahuan Siswa Tentang Permainan Bulutangkis Kelas VIII di SMP Negeri 1 Telukjambe Barat Kabupaten Karawang - Raafi Fadilla Majid; Rekha Ratri Julianti; Rahmat Iqbal (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to determine the level of knowledge of students about the game of badminton in class VIII at SMP Negeri 1 Telukjambe Barat, Karawang Regency. The research method uses a survey method with a questionnaire/questionnaire. Based on the results of the study, it can be concluded that the level of knowledge of students about the game of badminton in class VIII at SMP Negeri 1 Telukjambe Barat, Karawang Regency for the level of knowledge of students about the game of badminton is in the "enough" category by getting an average score (mean) of 17.04 of the overall data taken in class VIII students in accordance with the assessment reference norms. Based on the indicators of the level of student knowledge about the game of badminton which has 4 categories, namely, understanding and benefits, basic techniques, history, and rules. In grade VIII students at SMP Negeri 1 Telukjambe Barat have a higher level of knowledge based on "understanding and benefits" by 21%, "basic techniques" by 32%, "history" by 14%, and "regulations" 33% so for the level of knowledge Students about the VIII grade badminton game at SMP Negeri 1 Telukjambe Barat have a higher level of knowledge based on the "rules" indicator by 33% because it is more dominant than other indicators. Thus the level of knowledge of students about the game of badminton in class VIII at SMP Negeri 1 Telukjambe Barat from the research data that has been carried out it can be concluded that the level of knowledge of students about the game of class VIII badminton at SMP Negeri 1 Telukjambe Barat, Karawang Regency is included in the "enough" category